Heat inactivation of Bacillus subtilis spores lacking small, acid-soluble spore proteins is accompanied by generation of abasic sites in spore DNA. - Setlow, B (1994)
Previous work has shown that lethal heat treatment of Bacillus subtilis spores lacking the major DNA-binding proteins SASP-alpha and -beta (alpha-beta- spores) causes significant DNA damage, including many single-strand breaks. In this work we have used a reagent specific for aldehydes present in abasic sites in DNA to show that DNA from wild-type spores killed by heat treatment to levels of < 0.05% survival had at most two aldehydes (i.e., abasic sites) per 10(4) nucleotides, while DNA from alpha(-)beta- spores killed to similar levels had 7 to 20 times as many abasic sites per 10(4) nucleotides. These data were generally consistent with the level of single-strand breaks in DNA from these heated spores and strongly suggest that a major mechanism responsible for the heat killing of alpha(-)beta- (but not wild-type) spores is DNA depurination followed by strand breakage at the resultant abasic site. In contrast, hydrogen peroxide killing of alpha(-)beta - spores was not accompanied by generation of a high level of DNA aldehydes.